Farmers’ perception of mechanical rice seedling transplanter in Edu and Pategi Local Government Areas of Kwara State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2025)
This study assessed rice farmers' perceptions of mechanical rice seedling transplanters in Kwara State, Nigeria. A multi-stage sampling procedure was used to select 150 rice farmers from Edu and Pategi Local Government Areas. Data were analysed using percentage and Pearson correlation. Results showed that most farmers (94.7%) had very high positive perceptions of mechanical transplanters, recognizing benefits like reduced seedling wastage, faster planting, labour savings, and improved crop uniformity. However, accessibility remained limited, with only 3.3% accessing government subsidies and 24.7% having finance to procure transplanters. Major challenges included inadequate funding, poor technical knowledge, and high maintenance costs. Significant relationships were found between farmers' perceptions and socioeconomic factors like age, farming experience, farm size, and income. While perceptions were positive, actual adoption was low due to accessibility barriers. Recommendations include expanding subsidies and training programs, developing targeted financial products, and formulating mechanization policies accounting for socioeconomic influences on adoption.
Keywords: Adoption; Farm size; Influence; Maintenance; Manual